2012
DOI: 10.4236/ojoph.2012.23018
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Endophthalmitis Associated with Facial Cellulitis After a Tongue Bite

Abstract: Endogenous endophthalmitis is an intraocular infection that results from hematogenous spread of organisms from a distant source of infection. Facial cellulitis is rarely reported as a focus of infection. We report a case of 51-year-old unconscious woman presenting with fever, facial swelling, and decreased visual acuity secondary to facial cellulitis, endogenous endophthalmitis and end-stage renal disease (ESRD). Generally systemic antibiotics in endophthalmitis have low efficacy because of the blood-ocular ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Orbital and peri-orbital cellulitis have been reported as causes of endogenous endophthalmitis. [8,37] Facial cellulitis is rarely reported as a focus of infection leading to endogenous endophthalmitis. Facial cellulitis usually appears more rapidly than other deep infections, so treatment is required early on.…”
Section: Orbital and Peri-orbital Cellulitis As A Cause Of Endogenousmentioning
confidence: 99%
See 2 more Smart Citations
“…Orbital and peri-orbital cellulitis have been reported as causes of endogenous endophthalmitis. [8,37] Facial cellulitis is rarely reported as a focus of infection leading to endogenous endophthalmitis. Facial cellulitis usually appears more rapidly than other deep infections, so treatment is required early on.…”
Section: Orbital and Peri-orbital Cellulitis As A Cause Of Endogenousmentioning
confidence: 99%
“…These anatomical characteristics explain how facial cellulitis can be a primary infection site of endogenous endophthalmitis. Kang et al, [8] reported a case of 51-year-old unconscious woman presenting with fever, facial swelling, and decreased VA secondary to facial cellulitis, endogenous endophthalmitis and end-stage renal disease. These authors reported successful treatment with intra-vitreal (Vancomycin, Ceftazidime) and intravenous antibiotics (Vancomycin, Meropenem).…”
Section: Orbital and Peri-orbital Cellulitis As A Cause Of Endogenousmentioning
confidence: 99%
See 1 more Smart Citation